Pattern of mobile phone usage among fishermen in Pangkor Island - Mohamed Shaffril, Hayrol Azril; Omar, Siti Zobidah; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva (Universiti Putra Malaysia, 2012)
Mobile phone has emerged as one of the important tools in this digital era. It has benefited various groups of community and fishermen are one of them. The main attempt of this paper is to identify the pattern of mobile phone usage among fishermen in Pangkor Island in Malaysia. This study is quantitative in nature where a total of 250 of Pangkor Island fishermen were selected as the respondents. Findings have confirmed that though majority of the fishermen do not spend so much time and money for making and receive calls and SMS/MMS, mobile phone is still a crucial fisheries tool for them particularly on its role in strengthening their safety and ease their communication process with their family while conducting their fishing operation. Albeit mobile phone superior functions in marketing, fishermen in Pangkor Island seem to place less interest on it. A number of discussions have been highlighted whereby it is a hope that it can provide ideas for the concern parties in maximizing mobile phone benefits for the fishermen.